General practitioners in front of COVID-19: Italy in European comparative perspective - Genova, Angela; Lombardini, Simone (Frontiers in Sociology, 2024)
COVID-19 has highlighted strengths and weaknesses in healthcare systems all over the word. Despite the differences in primary care models in Europe, this study investigates the state-of-the-art of general practitioners (GPs) before the COVID-19 pandemic spread as a result of the reform process of the previous two decades. The GPs numbers over 100,000 inhabitants has been considered as a proxy of public health investment in GPs. Is the number of GPs increased or decreased in the last 20 years of reform processes in European countries? The main hypothesis is that European healthcare systems would have increased the number of GPs coherently with WHO recommendations. Comparative data on the number of GPs per 100,000 inhabitants in 21 European countries are investigated between 1995 and 2014 (the last available data). Data show that the number of family doctors over 100,000 inhabitants in European countries has increased over the last 20 years, except for Italy, where it has strongly reduced. Primary care has had a crucial role in managing the pandemic. Results of this study suggest that a country such as Italy, which has not invested in family doctors in the last two decades, would have been less equipped to manage the COVID-19 pandemic.